Conch Blowing Ameliorates Obstructive Sleep Apnea - Rajeev Gupta , Shiva Ahuja , Nishant Gupta (RUHS Journal of Health Sciences, 2023)
Obstructive sleep apnea is a major health problem in adults and leads to a variety of cardiovascular, respiratory, neurocognitive and metabolic problems. Continuous positive airway pressure is therapy of choice. All treatments have low adherence rates. Given the pathogenic importance of oropharyngeal muscles we hypothesized that conch blowing could be useful for improving its severity. A50-year old gentleman presented to us with daytime somnolence and excessive snoring. Physical examination showed body mass index of 32.0 2 kg/m with normal examination. Polysomnography showed apnea-hypopnea index of 78.0 and oxygen desaturation index of 74.8. He refused positive airways pressure therapy. He was advised conch blowing, 5 times twice daily. At 12 months follow-up his daytime 2 somnolence decreased, body mass index was 30.8 kg/m , apnea-hypopnea index was 50.6, and oxygen desaturation index was 43.7. Mechanistic studies and randomized controlled trials are required to demonstrate benefits of conch blowing in obstructive sleep apnea.